WAYS TO INTRODUCE AND DEVELOP ISLAMIC BANK PRODUCTS IN THE BANK BUSINESS - Иноятова Камола Фуркатовна (European Science Publishing, 2025)
The article shows how the Islamic financial structure is applied by commercial banks in Uzbekistan and analyzes the development of assets around the world.
Keywords: Islamic banks, banking system, assets, financial resources, banks.